The Choral [videorecording (DVD)] - Bennett, Alan, 1934-; Fiennes, Ralph; Allam, Roger; Addy, Mark, 1964-; Armstrong, Alun; Emms, Robert, 1986-; Marshal, Lyndsey; Cook, Ron, 1948-; Beale, Simon Russell (Sony Pictures Classics, 2026)
1916. As war rages on the Western Front, the Choral Society in Ramsden, Yorkshire has lost most of its men to the army. The Chloral's ambitious committee, determined to press ahead, decides to recruit local young males to swell their ranks. They must also engage a new chorus master, and despite their suspicions that he has something to hide, their best bet seems to be Dr. Henry Guthrie driven, uncompromising, and recently returned from a career in Germany. As conscription papers start to arrive, the whole community discovers that the best response to the chaos that is laying waste to their lives is to make music together.